(untitled) (Progressive Agriculture, 2019)
A field experiment was conducted in the farmer’s field at Salaipur, Mithapukur, On Farm Research Division, Rangpur during 2015-2016to control cucurbit fruit fly effectively through the use of sex pheromone trap. The trial was conducted among six farmers. Three treatments viz., T1 (Sex pheromone + Poison bait + Sanitation (9 spot)), T2 (Sex pheromone + Poison bait + Sanitation (16 spot)) and T3 (Farmers practice) were compared. The total land area was 7200m2. The higher fruit yield (63.99t/ha) was obtained from T2 (Sex pheromone + Poison bait + Sanitation (16 spot). The lower fruit yield (27.99 t/ha) was obtained from T3. The gross margin (Tk. 294706/ha) and gross return was also higher with the use of T2 (Sex pheromone + Poison bait + Sanitation (16 spot).The highest gross margin and gross return was found in T2 (Sex pheromone + Poison bait + Sanitation (16 spot) treatment. Use of insect lures can improve safe vegetable production as well as yield. Innovative agricultural technologies have the potential to increase yield and income of smallholder vegetable farmers in the northern region of Bangladesh. Progressive Agriculture 30 (2): 150-156, 2019